Recurrence of breast carcinoma as Paget disease of the skin at a prior core needle biopsy site: Case report and review of the literature. (2015) - Calvillo, Katherina Zabicki; Guo, Lifei; Brostrom, Valerie; Schnitt, Stuart J.; Hong, Xuefei; Raza, Sughra; Lester, Susan C.
Highlights: Recurrence of breast cancer at the site of a prior core needle biopsy after definitive surgery is very rare—only 13 cases have been reported. The majority are recurrent invasive cancers forming palpable masses in dermis and subcutaneous tissue at the skin puncture site of the core needle biopsy. Diagnosis can be delayed if a lesion is not initially recognized as being at a needle biopsy site. We report the first case of needle puncture site recurrence as Paget disease of the epidermis (ductal carcinoma in situ). It is important to document the site of the skin puncture of a needle biopsy to aid in early detection, and recognition, of needle track recurrences. Abstract: Introduction: Core needle biopsy has become the preferred method of diagnosing breast carcinomas prior to definitive surgery. The possibility of displacing tumor cells into the needle track is a concern. Presentation of case: A 38 year old woman was diagnosed with right breast ductal carcinoma in situ (DCIS) with microinvasion by core needle biopsy. Bilateral skin sparing mastectomies with immediate autologous reconstruction were performed. One and a half years later the patient noted erythema and a scaling crust on the skin of the right breast that progressed over several months. Punch biopsy revealed Paget disease restricted to the epidermis. Subsequent comparison to initial clinical photographs confirmed the cancer was associated with the skin puncture site of the needle biopsy. The patient underwent complete excision with skin grafting and remains free of disease three years later. Discussion: Only 13 cases of needle track recurrences have been reported. The majority presented as invasive carcinoma forming a subcutaneous mass. In the current case, detection was delayed due to not initially noting that a skin lesion was at the puncture site of the original needle biopsy. This is the only case of recurrence as tumor limited to the epidermis. Conclusion: Although recurrence in a needle track occurs very infrequently, clinicians should be aware of this phenomenon and investigate any changes, particularly when occurring at a needle biopsy site. Recording the skin puncture site can aid in early detection of recurrences. Recognition of a recurrence is important for prompt treatment and optimal prognosis.